2010
DOI: 10.1016/j.otohns.2009.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Neck restaging with sentinel node biopsy in T1‐T2N0 oral and oropharyngeal cancer: Why and how?

Abstract: The SN biopsy technique appeared to be the best staging method in cN0 patients and provided evidence that routinely undiagnosed lymph node invasion may have clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 20 publications
0
23
1
2
Order By: Relevance
“…The year after the publication by Morton et al, Alex et al [4] described a peritumoral intradermal injection of radioactive tracer ( 99m Tc-sulphur-colloid), integrating preoperative imaging and intraoperative gamma probe radiolocalization of SLNs in just one procedure. The SLN concept has since been extensively studied and validated for patients with cutaneous melanoma [27] and breast cancer [28], and studies to date have indicated a high level of accuracy in patients with OSCC [29, 30]. …”
Section: Background and Definitionsmentioning
confidence: 99%
“…The year after the publication by Morton et al, Alex et al [4] described a peritumoral intradermal injection of radioactive tracer ( 99m Tc-sulphur-colloid), integrating preoperative imaging and intraoperative gamma probe radiolocalization of SLNs in just one procedure. The SLN concept has since been extensively studied and validated for patients with cutaneous melanoma [27] and breast cancer [28], and studies to date have indicated a high level of accuracy in patients with OSCC [29, 30]. …”
Section: Background and Definitionsmentioning
confidence: 99%
“…For example, elective neck dissection is currently recommended for all HNC patients with an occult metastatic rate greater than 20% to 30%, (30), which actually might not be necessary for 60% to 70% of patients (31,32) and is associated with high risks and morbidity (33)(34)(35). The standard technetium-99-based SLN biopsy procedure currently suffers from several limitations, including lack of real-time intraoperative visual information (36)(37)(38). PLPs offer a promising method for accurately detecting malignant SLNs with preoperative PET/CT imaging and complementary fluorescence imaging for noninvasive diagnosis, preoperative stratification, and more accurate cancer staging.…”
Section: Discussionmentioning
confidence: 99%
“…The concept employs the detection and later biopsy of the first station of lymph nodes draining a specific anatomical site. SLN has not gained great popularity in the nodal management of head and neck tumors due to the variability in the lymph drainage from the respected anatomical sub-sites and thus is not an established standard of care [88][89][90][91].…”
Section: Neck Node Image Guided Surgerymentioning
confidence: 99%